Effects of genotype-by-environment and analysis of potential management interaction on vase life in cut lisianthus - Kim, Steven; Heo, Seong (Frontiers in Plant Science, 2025)
This research aimed to analyze how different genotypic and environmental conditions, along with salicylic acid (SA) treatment (management), influence the longevity of cut lisianthus flowers during post-harvest period. Four genotypes (“Arena Green”, “Blue Picote”, “Corelli Pink”, or “Kroma White”), four environments (hydroponic or soil cultivation with SA treatment during vegetative or reproductive period), and four levels of managements (SA concentration at 0, 0.1, 0.3, or 0.5 mM) were analyzed using the additive main effects and multiplicative interaction model (also known as AMMI model) and linear mixed-effects regression models. The biplot and linear mixed-effects regression analysis showed that hydroponic cultivation with SA treatment during the reproductive period was the most effective environment for prolonging the vase life. It appeared that higher SA concentrations increased the vase life on average, but the effect of SA management depended on genotype and environment. In addition, the regression analysis revealed that dry weight and the interaction between petal number and petal size, among all measured vegetative and reproductive variables, were significantly related to the vase life. The regression lines indicated that the expected vase life increases with respect to the petal size when the petal number is low, but decreases when the petal number is high. In conclusion, genotype-specific cultivation and management is needed for enhancing the vase life of cut lisianthus flowers, and balance between petal size and petal number is also crucial. The findings suggest that an optimal strategy for improving the vase life depends on the environment, management, and genotype.